Additional Magnetic Resonance or Nuclear Scintigraphy Imaging Influences Approach to Vertebral Augmentation: A Single Institution Experience. Issue 15 (1st August 2020) - Martin, Jonathan G.; Goldman, Daryl T.; Dabrowiecki, Alexander M.; Newsome, Janice; Bercu, Zachary L.; Gilliland, Charles
Abstract : Study Design: Retrospective review. Objective: To ascertain impact of preprocedural magnetic resonance imaging (MRI) or nuclear medicine Tc99m-DMP scintigraphy on the treatment plan when compared with plain films and/or computed tomography prior to vertebral augmentation procedures. Summary of Background Data: Over 1 million vertebral compression fractures (VCFs) occur in the United States annually with over 150, 000 individuals hospitalized each year. Physical examination and history are essential to the workup of VCFs, but imaging remains necessary for confirming the diagnosis. VCFs can be imaged with various modalities and there is limited data on the comparative effectiveness of different imaging modalities. Methods: Six hundred fifty consecutive patients treated with vertebral augmentation at a single institution between May of 2013 and April of 2018 were reviewed. Preprocedure imaging of the spine obtained within 30 days prior to the procedure were reviewed. Preprocedure imaging results were cross-referenced against the levels treated by vertebral augmentation to determine whether there was a change in the levels treated after receiving an MRI or NM imaging study. Results: Three hundred sixty-three patients had adequate imaging for inclusion. One hundred fifty-four of these 363 patients (42.4%) had an alteration of their treatment plan based upon the MR or NM imaging. Fewer vertebral levels were treated in 33, different levels were treated in 41, and more levels were treated in 80 patients. Conclusion: MRI or nuclear medicine bone scan imaging prior to vertebral augmentation altered the location and number of levels treated in a large percentage of patients, adding specificity to treatment over findings on radiographs or computed tomography alone. Level of Evidence: 3 Abstract : Retrospective review of preprocedure imaging of 650 patients treated with vertebral augmentation was performed. Imaging results were compared to treated levels. CT and/or radiographs were compared to MRI and/or NM. Of 363 patients with adequate imaging for evaluation, 42.4% had an alteration of their treatment plan based upon the MR/NM imaging.